Identification of Potential Isolate Phosphate Solubilizing Bacteria Used 16S rRNA Gene - Sembiring, Albert; Sumanto, Natalia Lusianingsih (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Plants always interact with microorganisms either negatively or positively during their life cycle. The Phosphate Solubilizing Bacteria (PSB) group is one example that has some beneficial effects on the plant. PSB can transform insoluble soil inorganic phosphates into soluble phosphorous so plants can absorb them. This research aimed to test the isolate’s ability to solubilize phosphorous and use the 16S rRNA marker gene to identify it. Testing the ability of bacteria to solubilize phosphorous on Pikovskaya’s agar medium used a qualitative method by observing the halo zone in the colony around it. Then the bacterial isolate was identified by analyzing the result of sequencing the 16S rRNA gene. The RZ02 bacterial isolate showed the highest performance in solubilizing phosphorous, with a 9.1 mm solubilization index. The gene of 16S rRNA was carried out by using primers 27F and 1492R with an amplicon size of 1500 base pairs. Sequencing analysis and construction of a phylogeny tree were conducted by the Mega X neighbor-joining method and showed 100% similarity with Pseudomonas aeruginosa OIS 481. The solubilization index indicated that the bacteria had a potential candidate to be one of the inoculant components for biofertilizer.